Study on cracking mechanism and key parameters of roof in gob-side entry retaining by pre-split blasting roof in deep mine - Xiao Liu; Xueqiu He; Yuntao Liang; Xinzhu Hua; Chen Li (Energy Exploration & Exploitation)
Based on 7135 working face of Qidong Coal Mine, the cracking mechanism of pre-splitting of gob-side entry retaining by roof cutting and the key parameters of pre-splitting blasting are studied by means of theoretical analysis, numerical simulation, and on-site measurement. Under the same blasting conditions, the energy of shaped-charge blasting in the direction of shaped charge is much larger than that of non-shaped-charge blasting, and the cracks generated along the direction of shaped charge are longer than that of non-shaped-charge blasting. The key parameters of pre-splitting cracks are the hole spacing and charge length. The crack propagation law of two holes blasting at the same time with different blasting methods, different linear charge density, and different hole spacing is studied. It is obtained that the cracking effect of shaped-charge blasting with the same hole spacing is better than that of non-shaped-charge blasting, showing that it can form part-through cracks; Increasing the linear charge density can increase the crack distance, but also destroy the integrity of the retained rock mass. The key parameters of advanced pre-splitting blasting in engineering practice are put forward. Generally, the maximum hole spacing and the minimum charge length that can produce part-through cracks are selected. When the hole spacing is 600 mm and the charge length is 4 m, the crack propagation of roof and the stress change of anchor cable after blasting are measured, and the crack formation rate reaches 86% to 90% within the blasting depth of blasting hole, and the anchor cable is in a good stress state, which can effectively control the roof. The research results provide a theoretical basis for the parameter design of pre-splitting blasting cracking of gob-side entry retaining by roof cutting.